Cognitive and psychosocial predictors of everyday function: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Farias, Sarah Tomaszewski; Eng, Chloe W.; Chan, Michelle L.; Gilsanz, Paola; Whitmer, Rachel A.
Abstract: Background: Subtle declines in functional abilities, including difficulties completing instrumental activities of daily living (IADLs; e.g., managing finances), can be very early indicators of Alzheimer's Disease and related disorders (ADRD). Cognitive difficulties are major determinants of IADL difficulties, but account for less than half the variance in performance. Psychosocial variables, such as depression, loneliness, and perceived emotional support may also influence a person's functional status independent of their cognition. The present study examined cognitive and psychosocial predictors of IADL functioning across an ethnoracial diverse cohort. Method: The Kaiser Healthy Aging and Diverse Life Experience (KHANDLE) cohort is comprised of Kaiser Permanente Northern California members (approximately even proportions of Caucasians, African Americans (AA), Asians, and Latinos) who are age ≥65, without a diagnosis of cognitive impairment or dementia, and who participated in Multiphasic Health Checkups between 1964‐1977. At enrollment, participants completed a self‐report measure of IADL, neuropsychological testing measuring memory and executive functioning, and psychosocial questionnaires measuring depression, loneliness, and emotional support. Analyses include 1, 485 participants (448 Caucasian (30.2%), 386 AA (26.0 %), 362 Asian (24.4%), and 289 Latino (19.5%). Cox proportional hazards models estimated the associations between psychosocial factors and cognitive domains overall and within ethnoracial groups. Result: Average baseline age was 75.6 and 59.6% were female. AA were less likely to report excellent/very‐good heath (30.1%) verses Caucasians (50.4%), Asians (45.0%), and Latinos (45.3%). After controlling for age, education, gender, and self‐rated health, loneliness predicted IADL performance independent of both memory (p<0.0001) and executive functioning (p<.0001). Emotional support predicted IADLs, independent of memory (p=0.0048) and executive functioning (p=0.0098). Depression was not independently associated with IADLs. Relationships were similar across the four ethnoracial groups. Conclusion: Few studies have simultaneously examined cognitive and psychosocial predictors of IADLs across such a diverse group of older adults. Our study indicates that greater loneliness and lower perceived emotional support are associated with worse IADL function, independent of cognitive performance across ethnoracial groups. While the directionality of these relationships need further study, interventions aimed at decreasing social isolation may ultimately help to keep individuals functioning more independently in their daily lives.